TEKNIK PENGAMBILAN GAMBAR DALAM PRODUKSI FEATURE BERITA TELEVISI “SETENGAH HATI KURANGI PLASTIK” - Khalishah Nuramalina (Jurnal Visi Komunikasi, 2022)
Feature included in journalistic products that explain the problem in depth and sharp but with an interesting and mild language style. The television news feature ‘Setengah Hati Kurangi Plastik’ carries the theme of environmental issues that focus on the problem of plastic waste, which is a serious problem in the world including Indonesia. The results of research from researchers from the University of Georgia, United States, Dr. Jenna Jambeck, Indonesia is the second of 192 countries that produce the most plastic waste in the world. While the title 'Half a Heart Reduce Plastic' is a satirical word aimed at people who are still half-hearted in their commitment to reduce the use of plastic. In addition, government regulations are also considered not to be a solution and are still applied unevenly. In making this work, the writer acts as a Camera Person. The shooting technique used is The Developing Shot technique, where this technique is a combination of all the elements contained in the camera, such as lens movement, camera movement, mounting movement.